Fundamental motor skills in preschoolers participating in a Developmental Physical Education program: preliminary results of a descriptive cross-sectional study - Briet, Rafael N. (2025)
BACKGROUND: Many studies indicate delays in the motor development of Brazilian preschoolers. These delays may be partly attributed to the sporadic presence of physical education teachers in early childhood education and the lack of preschoolers’ participation in physical activity programs focused on developing these skills. AIM: To investigate the gross motor quotient and motor age of children participating in a Developmental Physical Education program. METHODS: The Test of Gross Motor Development (TGMD-2) was used to assess the motor developmental level of 19 children enrolled in an early childhood education center. Participants were divided into three age groups: three, four, and five years old. RESULTS: After 12 weeks of classes, all participants demonstrated acceptable motor development, with a motor age at or above their chronological age. Thirteen children (68.42%) received average descriptive ratings, three (15.8%) received above-average ratings, and three (15.8%) received superior ratings. INTERPRETATION: Participation in a systematic and regular Developmental Physical Education program appears to support the acquisition and refinement of fundamental motor skills in young children.